“Os corpos cercados” and poetic concentration field - Vitagliano, Karina Marize; Piteri, Sônia Helena de Oliveira Raymundo (ITINERÁRIOS – Revue de Littérature, 2008)
The potentialities of writing in the short story “Os corpos cercados”, in Os pregos na erva (1962), of Maria Gabriela Llansol, are made evident by means of “cenas fulgor” (a term coined by of the author) and by the permeability of the boundaries among literary genres, resulting in a text in which the short story dialogues with poetry. This hybrid aspect displaces narrativity to textuality, as it devises a plot that is built by a quasi-total absence of action, whereas the experimentation process with language dominates. The textual space suggests a concentration camp that superimposes bodies, sounds, rhythm and images. Thus, this paper aims at showing how salient lyrical moments affect the structure of Llansol’s short story, once peculiar aspects of prose give way to the outburst of sonority and expressivity.